Pengaruh Work Life Balance, Stres Kerja dan Kepuasan Kerja Terhadap Kinerja Perawat Rumah Sakit Mata Undaan - Rizaldi, Muhammad; Santoso, Bowo (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
The purpose of this research is to find out how work life balance, work stress and job satisfaction affect the performance of nurse at the Undaan eye Hospital in the city of Surabaya. This research method is quantitative by taking sample of 73 respondents. The collection techinique uses purposive sampling. The sample consisted of the performance of nurses at the Undaan eye Hospital. The analysis technique used in this research is (PLS) with validity testing, reliability testing and hypothesis testing. The result of this research prove that: (1) work life balance has a positive and significant effect on nurse performance. (2) work stress has a positive and significant effect on nurse performance. (3) job satisfaction has a positive and significant effect on nurse performance.